The moment of tenderness - L'Engle, Madeleine (Grand Central Publishing, 2020)
"This powerful collection of short stories traces an emotional arc inspired by Madeleine L'Engle's early life and career, from her lonely childhood in New York to her life as a mother in small-town Connecticut. In a selection of eighteen stories discovered by one of L'Engle's granddaughters, we see how L'Engle's personal experiences and abiding faith informed the creation of her many cherished works. Some of these stories have never been published; others were refashioned into scenes for her novels and memoirs. Almost all were written in the 1940s and '50s, from Madeleine's college years until just before the publication of A Wrinkle in Time. From realism to science-fiction to fantasy, there is something for everyone in this timeless, magical collection"--Provided by publisher.